Mengupas Type Models, Frameworks, Dimensi, dan Definisi: Literatur Review Entrepreneurial Marketing 10 Tahun Terakhir - Adjie Ahmad Darajat; Muhammad Rizal; Ria Arifianti (Universitas Winaya Mukti, 2020)
Research on Marketing and Entrepreneurship has been developing for years, even now. Entrepreneurial Marketing (EM), was born from the practice of companies operating in conditions of uncertainty and emerged as a compelling alternative to overcoming the declining effectiveness associated with traditional marketing practices. In this article, the author provides a comprehensive review of the type models, frameworks, dimensions, and definitions. In total, three types of research interest: first, related research related to the range of the development of the concept of EM type models and EM frameworks, second, to explore the development of EM dimensions, the third to explore the comparison of definitions, the difference between EM and traditional marketing in EM research in the last ten years.